Meet Naiche A Native Boy from the Chesapeake Bay Area - Tayac, Gabrielle (Council Oak Books, 2002)
Details a day in the life of a rural Maryland boy of Piscataway and Apache descent, looking at his family, the history of his tribe, and some traditional ceremonies and customs that are still observed today.
Keywords: Juvenile Non-Fiction / Biographies